Culinary Development Strategy for Traditional Japanese Food (Moci) in Bengkulu City by Utilizing Digital Technology - Fatanah, Jihan; Indriani , Putri; Azizah, Fadilla Nur (JENTIK : Jurnal Pendidikan Teknologi Informasi dan Komunikasi, 2023)
Digital marketing strategy is a form of marketing that utilizes digital media. Several digital media that currently have the potential to be used as digital marketing media are social media. Some of the social media most widely used by Indonesian people are WhatsApp, Instagram, Facebook, TikTok and Telegram. Social media has been proven to play a big role in the world of product marketing. Therefore, researchers conduct research that aims to describe conditions related to the influence of digital marketing in increasing product sales. The object of research is the mochi cake business in Djapuan Mochi. In this research, researchers used descriptive methods to describe problems that were occurring at this time or that were ongoing at the time the research was conducted. The research instrument used was an interview sheet. The research results show that with a marketing strategy using digital media, you can market your product in Djapuan Mochi become broader and can reach more consumers. From the results of this research, it can be concluded that digital marketing can increase product sales in Djapuan Mochi.